TEKTUALISASI DAN KONTEKTUALISASI AJARAN ISLAM DALAM AL-QURAN/HADIS - Ernawati; Andi Aderus; Muh. Amri (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
Textualization and contextualization of Islamic teachings in the Quran and Hadith refer to two important approaches in understanding and applying Islamic teachings in the context of the times and human life. This textualization refers to understanding the holy texts, such as the Quran and Hadith, thoroughly and in depth. This process involves analyzing the linguistic, historical, and socio-cultural contexts in which the texts were revealed. For example, understanding the meaning of the Arabic words used in the Quran and identifying the historical context behind the revelations. Contextualization This includes connecting the teachings contained in the holy texts with contemporary realities and everyday life. This process is important to bridge the gap between timeless teachings and the challenges and changes of the times. An example is applying Islamic moral and ethical principles in the context of modern life, such as technological issues, globalization, and social issues. In practice, textualization and contextualization enable Muslims to better understand religious teachings, maintain the relevance of these teachings in various situations, and avoid erroneous or inappropriate interpretations. This also helps maintain continuity between religious traditions and developments in the era, so that Islamic values ​​can provide meaningful guidance for humanity in various eras.